2016
DOI: 10.1074/jbc.m115.699660
|View full text |Cite
|
Sign up to set email alerts
|

Cell Autonomous and Nonautonomous Function of CUL4B in Mouse Spermatogenesis

Abstract: CUL4B ubiquitin ligase belongs to the cullin-RING ubiquitin ligase family. Although sharing many sequence and structural similarities, CUL4B plays distinct roles in spermatogenesis from its homologous protein CUL4A. We previously reported that genetic ablation of Cul4a in mice led to male infertility because of aberrant meiotic progression. In the present study, we generated Cul4b germ cell-specific conditional knock-out (Cul4b Protein degradation via the ubiquitin-proteasome system plays a critical role durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…In several studies, it was shown that the CUL4 ubiquitin ligases (CUL4A and CUL4B) play essential roles in male germ cell development. Both Cul4A and Cul4B mutant male mice were infertile 22 25 . Although CUL4A and CUL4B share sequence and structural similarities, both the proteins play diverse roles in spermatogenesis 23 25 , 47 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In several studies, it was shown that the CUL4 ubiquitin ligases (CUL4A and CUL4B) play essential roles in male germ cell development. Both Cul4A and Cul4B mutant male mice were infertile 22 25 . Although CUL4A and CUL4B share sequence and structural similarities, both the proteins play diverse roles in spermatogenesis 23 25 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Although CUL4A and CUL4B share sequence and structural similarities, both the proteins play diverse roles in spermatogenesis 23 25 , 47 . Disruption of Cul4A in mice resulted in male infertility due to abnormal meiotic progression, whereas disruption of Cul4B in mice caused male infertility because of aberrant post-meiotic sperm development 22 25 . Macroscopic features of Cul4A KO mice testes showed two fold reductions in the size and the weight of the Cul4A −/− testis compared to that of wild type 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strikingly, cul4a null mice are hyper-resistant to UV-induced skin cancer (15). CUL4A and CUL4B are also expressed at different stages of spermatogenesis, and germ line deletion of either cul4 gene results in male infertility (24,27). Therefore, CUL4A and CUL4B share overlapping functions in growth and survival, while also playing distinct roles in diverse cellular processes.…”
mentioning
confidence: 99%